A Review of Sustainable Water Practices: Teaching High School Students to Manage and Purify Water for Daily Needs - Prayogo, Wisnu; Ihsan, Muhammad Faris; Awan, Fajriharish Nur; Mawaddah, Nurul; Khairuni, Zhilli Izzadati; Wibowo, Harry; Atika, Liana; Trimailuzi; Tinov, Naufal; Rahmadani, Sarra; Maulida, Fatimah; Lukman, Mena Fadillia (CV. Literasi Indonesia, 2024)
Access to clean and safe water is a fundamental human need, yet millions of people around the world still lack reliable sources of potable water. Educating high school students about sustainable water practices is crucial to ensuring that future generations are equipped to manage and purify water resources effectively. This review examines the importance of teaching water management and purification to high school students, with a focus on practical, low-cost methods that can be implemented using simple tools and techniques. The review explores various hands-on approaches to water education, including basic water quality assessment, filtration methods, and affordable purification technologies such as sand filtration, boiling, and solar disinfection. It also highlights the pressing global issue of water scarcity, noting that over 2 billion people still rely on unsafe drinking water sources. In addition to theoretical knowledge, students engage in fieldwork and laboratory experiments, where they test and treat local water sources, gaining practical experience with real-world water challenges. By the end of the program, students are equipped with the knowledge and skills to identify safe water sources and apply basic treatment methods for daily use, such as drinking, cooking, bathing, and sanitation. The initiative aims to foster environmental awareness, encourage responsible water use, and promote community-driven solutions to water scarcity and contamination, empowering students to contribute to sustainable water practices in the future.